Linking adult olfactory neurogenesis to social behavior - Feierstein, Claudia E. (Frontiers in Neuroscience, 2012)
In the adult brain, new neurons are added to two brain areas: the olfactory bulb and the hippocampus. Newly-generated neurons integrate into the preexisting circuits, bringing a set of unique properties, such as increased plasticity and responsiveness to stimuli. However, the functional implications of the constant addition of these neurons remain unclear, although they are believed to be important for learning and memory. The levels of neurogenesis are regulated by a variety of environmental factors, as well as during learning, suggesting that new neurons could be important for coping with changing environmental demands. Notably, neurogenesis has been shown to be physiologically regulated in relation to reproductive behavior: neurogenesis increases in female mice upon exposure to cues of the mating partners, during pregnancy and lactation, and in male mice upon exposure to their offspring. In this scenario, and because of the key contribution of olfaction to maternal behavior, we sought to investigate the contribution of adult-generated neurons in the olfactory system to maternal behavior and offspring recognition. To do so, we selectively disrupted neurogenesis in the olfactory pathway of female mice using focal irradiation. Disruption of adult neurogenesis in the olfactory bulb did not affect maternal behavior, or the ability of female mice to discriminate familiar from unfamiliar pups. However, reduction of olfactory neurogenesis resulted in abnormal social interaction of female mice, specifically with male conspecifics. Because the olfactory system is crucial for sex recognition, we suggest that the abnormal interaction with males could result from the inability to detect or discriminate male-specific odors and could therefore have implications for the recognition of potential mating partners. Here, I review the results of this and other studies, and discuss their implications for our understanding of the function of adult neurogenesis.